“DESA KARYA” SEBUAH KAJIAN UNTUK MENGURANGI TINGKAT PENGANGGURAN DI PEDESAAN (STUDI PADA KOMUNITAS PANDAI BESI DI DESA KAJAR, GUNUNG KIDUL, YOGYAKARTA) - Hendri Hermawan Adinugraha; Sih Darmi Astuti; Mila Sartika (Universitas Serang Raya, 2016)
To date, unemployment rate in Gunung Kidul has been a problem that can not be resolved optimally . The emergence of new ways to tackle poverty certainly was needed by all takeholders.This research is descriptive library research. The writer used descriptive approach and the writer used an interactive models as analysis techniques. The purpose of this research was to determine the intent of “Desa Karya”, in order the Kajar villagers to be more creative skilled in the field of craft blacksmiths and to determine the contribution of “Desa Karya” in poverty reduction in rural areas. leteratur studies have been conducted in this research, it can be concluded that “Desa Karya” is a collection of people who is produce a product or service and actingsignificantly after the inventiveness and flavor process. Community to do something highly productive economically and materially. The implementation of “Desa Karya”concepts as blacksmith craftsman in Kajar will very potential to be formulated , due to the excellence work high quality products and had historical value . “Desa Karya” also able to reduce poverty and unemployment in rural areas